Extended UVB Exposures Alter Tumorigenesis and Treatment Efficacy in a Murine Model of Cutaneous Squamous Cell Carcinoma - Erin M. Burns; Kathleen L. Tober; Judith A. Riggenbach; Donna F. Kusewitt; Gregory S. Young; Tatiana M. Oberyszyn (Journal of Skin Cancer)
Epidemiological studies support a link between cumulative sun exposure and cutaneous squamous cell carcinoma (SCC) development. However, the presumed effects of extended ultraviolet light B (UVB) exposure on tumorigenesis in the sexes have not been formally investigated. We examined differences in ultimate tumorigenesis at 25 weeks in mice exposed to UVB for either 10 or 25 weeks. Additionally, we investigated the effect of continued UVB exposure on the efficacy of topical treatment with anti-inflammatory (diclofenac) or antioxidant (C E Ferulic or vitamin E) compounds on modulating tumorigenesis. Vehicle-treated mice in the 25-week UVB exposure model exhibited an increased tumor burden and a higher percentage of malignant tumors compared to mice in the 10-week exposure model, which correlated with increases in total and mutant p53-positive epidermal cells. Only topical diclofenac decreased tumor number and burden in both sexes regardless of UVB exposure length. These data support the commonly assumed but not previously demonstrated fact that increased cumulative UVB exposure increases the risk of UVB-induced SCC development and can also affect therapeutic efficacies. Our study suggests that cessation of UVB exposure by at-risk patients may decrease tumor development and that topical NSAIDs such as diclofenac may be chemopreventive.